1991
DOI: 10.1159/000480554
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Morphine in Infant Monkeys

Abstract: We report the pharmacokinetics of morphine administered as intravenous boluses in newborn (<7 days) and 3- to 4-month-old macaque monkeys. Morphine was administered in a series of bolus doses until Pa(CO(2)) was elevated > 50 mm Hg. In newborns < 7 days of age, a mean dose of 1.4 mg/kg was required (range 0.75-2.8 mg/kg), and in the 3-month-olds, a mean dose of 1.88 mg/kg was required (range 1.5-2.5 mg/kg). The respiratory effects measured by Pa(CO(2)) and respiratory rate did not correlate with declining seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Protein binding of morphine was 11% in newborns, and 17% at 1 year of age,” which may allow more “free” morphine to cross the blood‐brain barrier. She concluded that “increased CSF morphine is a transient finding in infant macaques, which appears to reach young adult values by 1 month of age.” 15,16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein binding of morphine was 11% in newborns, and 17% at 1 year of age,” which may allow more “free” morphine to cross the blood‐brain barrier. She concluded that “increased CSF morphine is a transient finding in infant macaques, which appears to reach young adult values by 1 month of age.” 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…She concluded that "increased CSF morphine is a transient finding in infant macaques, which appears to reach young adult values by 1 month of age." 15,16 Ultimately, if opioids were to gain widespread use in pediatric clinical practice, safety had to be proven. Thus, Dr. Lynn asked, "Are infants and newborns sensitive or resistant to morphine-related respiratory depression"?…”
mentioning
confidence: 99%